2019
DOI: 10.20945/2359-3997000000126
|View full text |Cite|
|
Sign up to set email alerts
|

Prediction of gestational diabetes mellitus in the first trimester: comparison of maternal fetuin-A, N-terminal proatrial natriuretic peptide, high-sensitivity C-reactive protein, and fasting glucose levels

Abstract: Objective: We investigated the utility of maternal fetuin-A, N-terminal proatrial natriuretic peptide (pro-ANP), high-sensitivity C-reactive protein (hs-CRP), and fasting glucose levels at 11-14 gestation weeks for predicting pregnancies complicated by gestational diabetes mellitus (GDM). Subjects and methods: This prospective cohort study included 327 low-risk pregnant women who completed antenatal follow-up at a tertiary research hospital between January and April 2014. Maternal blood samples were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 39 publications
(53 reference statements)
1
19
0
2
Order By: Relevance
“…However, Kralisch et al ,15 Simjak et al ,16 and Farhan et al 11 found that fetuin-A levels did not differ between women with GDM and without at 28th, 29th and 28th–38th gestational weeks, respectively. Another previous study evaluated fetuin-A levels in the first trimester (11–14 gestational weeks), and lower fetuin-A levels were found in 29 women with GDM as compared with 59 healthy pregnant women 14. Limitations of these studies included cross-sectional evaluation at a single time point before the diagnosis of GDM and modest sample sizes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, Kralisch et al ,15 Simjak et al ,16 and Farhan et al 11 found that fetuin-A levels did not differ between women with GDM and without at 28th, 29th and 28th–38th gestational weeks, respectively. Another previous study evaluated fetuin-A levels in the first trimester (11–14 gestational weeks), and lower fetuin-A levels were found in 29 women with GDM as compared with 59 healthy pregnant women 14. Limitations of these studies included cross-sectional evaluation at a single time point before the diagnosis of GDM and modest sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Considering GDM shared the similar pathophysiological feature of insulin resistance with T2DM, and women with GDM were at high risk of developing T2DM in later life,10 it could be speculated that fetuin-A might also be an important biomarker involved in the pathogenesis of GDM development. However, so far, limited research on the correlation between fetuin-A and GDM yielded inconsistent findings 11–16. Some of them found significant differences in fetuin-A concentration between healthy pregnant and GDM group,12–14 while others did not 11 15 16.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fetuin-A inhibits insulin receptor signaling4 5 and is an endogenous ligand of toll-like receptor 4 promoting lipid-induced insulin resistance 6. Gestation diabetes mellitus (GDM), a condition characterized by elevated insulin resistance and impaired glucose tolerance in the second half of the pregnancy,7 has been associated with elevated maternal circulating fetuin-A levels in some but not all studies 8–10. There is a lack of data on whether there are alterations in fetal/cord blood fetuin-A concentrations in GDM.…”
Section: Introductionmentioning
confidence: 99%